Wind Speed Distribution Direct Approximation by Accumulative Statistics of Measurements and Root-Mean-Square Deviation Control - Romanuke, Vadim (Electrical, Control and Communication Engineering, 2020)
In order to accurately estimate wind farm output and subsequently optimise it, a method of wind speed distribution approximation is suggested. The method is based on period-by-period accumulation of wind speed measurements, transforming them into empirical probabilities, and observing the moving approximation to the expected power produced by the wind turbine or entire wind farm. A year is a minimal term during which wind statistics are to be accumulated. The sufficient validity and reliability of the wind speed distribution approximation is supported by controlling root -mean-square deviations and maximal absolute deviations with respect to the moving average of the expected power. The approximation quality can be regulated by adjusting constants defining the requirements to the moving deviations.